2021
DOI: 10.5888/pcd18.200553
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Examination of Factors Related to HPV Vaccination Promotion in Private Dental Settings, Iowa, 2019

Abstract: What is already known on this topic?Research has shown that dental providers are willing to be involved in HPV vaccine promotion, but little is known about factors related to that willingness. What is added by this report?Our research identified important factors to address in future programs to help dental providers in HPV vaccine promotion. Our results aid design for an intervention to educate parents, to recommend the vaccine, and to refer parents to local providers.What are the implications for public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Finally, while knowledge gaps exist for both dentists and dental hygienists, as shown in this study, there is evidence of the particular importance of focusing CE efforts for dental hygienists. Previous research identified dental hygienists as potentially being more effective educators and disseminators of this kind of information due to their longstanding relationships with parents [20]. Therefore, while all dental professionals should have access to CE opportunities to provide education on HPV vaccination and HPV-related cancers, it will be particularly important for dental hygienists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, while knowledge gaps exist for both dentists and dental hygienists, as shown in this study, there is evidence of the particular importance of focusing CE efforts for dental hygienists. Previous research identified dental hygienists as potentially being more effective educators and disseminators of this kind of information due to their longstanding relationships with parents [20]. Therefore, while all dental professionals should have access to CE opportunities to provide education on HPV vaccination and HPV-related cancers, it will be particularly important for dental hygienists.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team sent two follow‐up mailings between May and June 2019: a postcard reminder 10 days after the initial survey and a second survey at 3 weeks following the initial mailing. Additional details on the survey and results are detailed elsewhere [20]. To analyze survey data, frequencies and descriptive statistics for all variables were generated using IBM SPSS Statistics 23.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation